PERSEPSI MASYARAKAT TERHADAP PERILAKU PEMUDA YANG KECANDUAN JUDI ONLINE: IMPLIKASI BAGI PENDIDIKAN DASAR - ihsan M Algina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid development of digital technology has significantly transformed social life, particularly in the areas of entertainment and economic activities. One phenomenon that has increasingly emerged alongside this development is the widespread practice of online gambling among young people. Online gambling offers easy access, anonymity, and the promise of instant financial gain, making it attractive to youths who are in a transitional phase of identity formation. However, involvement in online gambling often develops into addictive behavior that generates negative consequences not only for individuals but also for families and the broader social environment. This study aims to describe public perceptions of youth addicted to online gambling, identify factors contributing to such behavior, and analyze the resulting social impacts. This research employed a qualitative descriptive approach using in-depth interviews with community leaders, parents, community members, and youths who were or had been involved in online gambling. The findings indicate that most community members perceive online gambling addiction as a deviant behavior that contradicts social and religious norms, although some still regard it as a private matter. Contributing factors include easy access to technology, peer influence, economic pressure, and weak family supervision. The social impacts include family conflict, decreased youth productivity, dishonest behavior, and declining participation in community activities. Therefore, collaborative efforts involving families, communities, educational institutions, and government policies are essential to prevent and address online gambling addiction among youths.